2019
DOI: 10.1051/e3sconf/20197502007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of GRACE satellite measurements over seismically active areas of the strongest earthquakes

Abstract: The study is devoted to the analysis of the features of the change in the parameter EWH (Equivalent Water Height) over the geoid from the satellite measurements of the GRACE space system in seismically active areas of the strongest underwater earthquakes. The GRACE satellite data archive was created. An interpretation of the disturbed state of the geomedium using digital maps of the spatial distribution of the parameter EWH is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…In our research, to solve the set tasks of the retrospective analysis and interpretation of GRACE data in seismically active regions of strong underwater earthquakes, a computational technique was proposed including the following stages: analysis of variations in the EWH parameter in the disturbed geoenvironment relative to the epicenter area; construction of digital maps of the EWH parameter distribution under the disturbed (EWH2) and background (EWH1) conditions relative to the focal zone; construction of a digital map of the distribution of the relative deviations EWH determined from the difference EWH = EWH2 -EWH1 in the study area; detection and description of the EWH characteristic relative to the location of the focal zone and hypocenter of the studied strongest earthquake; calculation of the geodynamic parameter H defined as the distance from the hypocenter to the position of the barycenter of the Earth-Moon system; estimation of the correlation coefficients between the series of the H and EWH values; refinement of the spatio-temporal characteristics of the focal zones of strong underwater earthquakes with respect to the identified anomalies in the distribution of the EWH parameter. In [11] we studied the processes of preparation of the strongest earthquakes in seismically active regions of the Pacific Ocean based on the created computational technique and analysis of digital EWH maps. It was revealed that during the preparation and relaxation of the earthquakes the equivalent water height above the geoid in seismically active regions changed significantly.…”
Section: Computational Technique For Constructing and Analyzing Digit...mentioning
confidence: 99%
“…In our research, to solve the set tasks of the retrospective analysis and interpretation of GRACE data in seismically active regions of strong underwater earthquakes, a computational technique was proposed including the following stages: analysis of variations in the EWH parameter in the disturbed geoenvironment relative to the epicenter area; construction of digital maps of the EWH parameter distribution under the disturbed (EWH2) and background (EWH1) conditions relative to the focal zone; construction of a digital map of the distribution of the relative deviations EWH determined from the difference EWH = EWH2 -EWH1 in the study area; detection and description of the EWH characteristic relative to the location of the focal zone and hypocenter of the studied strongest earthquake; calculation of the geodynamic parameter H defined as the distance from the hypocenter to the position of the barycenter of the Earth-Moon system; estimation of the correlation coefficients between the series of the H and EWH values; refinement of the spatio-temporal characteristics of the focal zones of strong underwater earthquakes with respect to the identified anomalies in the distribution of the EWH parameter. In [11] we studied the processes of preparation of the strongest earthquakes in seismically active regions of the Pacific Ocean based on the created computational technique and analysis of digital EWH maps. It was revealed that during the preparation and relaxation of the earthquakes the equivalent water height above the geoid in seismically active regions changed significantly.…”
Section: Computational Technique For Constructing and Analyzing Digit...mentioning
confidence: 99%
“…-уточнение пространственно-временных характеристик очаговых зон сильных подводных землетрясений. С помощью разработанной вычислительной методики и выполненного детального анализа цифровых карт распределения EWH осуществлен реанализ процессов подготовки сильнейших землетрясений в сейсмоактивных районах Тихого океана, произошедших за последние 20 лет [6]. При этом актуальными являются вопросы: пригоден ли EWH для уточнения геодинамических особенностей во время подготовки сильнейших землетрясений, а также можно ли использовать этот параметр в качестве характеристики для выявления связи напряженно-деформированного состояния геосреды и форшоковых процессов.…”
unclassified